Knowledge, attitudes, and practices regarding seasonal influenza vaccination during pregnancy in Costa Rica: A mixed-methods study. Issue 48 (15th November 2022) - Madewell, Zachary J.; Chacón-Fuentes, Rafael; Badilla-Vargas, Xiomara; Ramirez, Catalina; Ortiz, Maria-Renee; Alvis-Estrada, Juan-Pablo; Jara, Jorge
Highlights: 86% of postpartum women and 58% of prenatal care doctors vaccinated for influenza. Clinician recommendations and perceived benefits associated with vaccination. Educational attainment inversely associated with influenza vaccination. Not being offered the vaccine was most cited reason for non-vaccination. 93% of prenatal care physicians believed influenza vaccine causes flu-like symptoms. Abstract: Background: Influenza increases stillbirth risk, morbidity and mortality in pregnant women. Vaccination protects pregnant women against severe disease and indirectly protects their infants, but coverage among pregnant women remains low worldwide. We aimed to describe knowledge, attitudes, and practices (KAP) regarding seasonal influenza vaccination among postpartum women and prenatal care physicians in Costa Rica. Methods: We conducted cross-sectional KAP surveys to women one to three days after childbirth at Costa Rican Social Security Fund maternity hospitals, and obstetricians and general practitioners who provided prenatal care in 2017. Principal components analysis, multiple imputation, and logistic regression were used to examine associations between influenza vaccination and demographics, prenatal care, and sources of information—separately for postpartum women and physicians. We also held two focus groups of six healthcare workers each to further describe vaccination KAP. Results: We surveyed 642 postpartum women and 146 physicians in maternity hospitals in five Costa Rican provinces of whom 85.5 % (95 % CI: 82.6 %-88.0 %) and 57.9 % (95 % CI: 49.6 %-65.7 %) were vaccinated for influenza, respectively. Factors associated with influenza vaccination for postpartum women included tetanus vaccination (aOR: 3.62, 95 % CI: 1.89–6.92); received vaccination recommendations from clinicians during prenatal check-ups (aOR: 3.39, 95 % CI: 2.06–5.59); had other children in household vaccinated for influenza (aOR: 2.25, 95 % CI: 1.08–4.68); and secondary/university education (aOR: 0.15–0.31) with no formal education as reference. For postpartum women, reasons for vaccination were perceived benefits for mother and infant, whereas not being offered vaccines was most cited for non-vaccination. Most prenatal care physicians recommended influenza vaccines during prenatal check-ups but believed vaccination causes flu-like symptoms. Conclusion: Vaccination campaigns and provisions of free vaccines effectively increased knowledge and coverage among women in Costa Rica. To improve access, women should be offered vaccines during prenatal care appointments. Educating healthcare workers about vaccine benefits for themselves and patients is needed to mitigate safety concerns.